An analysis of reporting verbs in master’s dissertations - Shirley Banini; Ernest Kwesi Klu; Ramos Asafo-Adjei (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
This study was purposed on analyzing reporting verbs in the Literature Review sections of some master’s dissertations in the field of Government and Leadership at the University of Professional Studies Accra (UPSA) in Ghana from the 2017/2018 to 2021/2022 academic year. The study sought to answer the main research question – what is the nature of the reporting verbs used in some master’s dissertations of students of the UPSA in the field of Government and Leadership? 20 dissertations were conveniently selected, and the Literature Review sections were analysed for reporting verbs using Hyland’s (2002) taxonomy which involves Research Acts, Cognition Acts and Discourse Acts as the analytical framework. These dissertations altogether contained 1,044,076 words. Results showed that students used various reporting verbs belonging to – Research Acts (observe, find), Cognition Acts (believe, conceptualize) and Discourse Acts (report, discuss) in their dissertations. Discourse Act reporting verbs were predominant compared to Cognition Acts and Research Acts, implying that the students used more of the reporting verbs associated with their mental processes. It is concluded that lecturers using English language and Research Methodology need to train students more in the use of reporting verbs in order to have their writing more impactful.